Membrane-bound IL-2 improves the expansion, survival, and phenotype of CAR Tregs and confers resistance to calcineurin inhibitors - Kremer, Jakob; Henschel, Pierre; Simon, Daniel; Riet, Tobias; Falk, Christine; Hardtke-Wolenski, Matthias; Wedemeyer, Heiner; Noyan, Fatih; Jaeckel, Elmar (Frontiers in Immunology, 2022)
Regulatory T cells (Tregs) play an important role in the maintenance of immune homeostasis and the establishment of immune tolerance. Since Tregs do not secrete endogenous IL-2, they are especially dependent on external IL-2. IL-2 deficiency leads to lower Treg numbers, instability of the Treg phenotype and loss of immune regulation. After organ transplantation, patients are treated with calcineurin inhibitors (CNIs), which further limits available IL-2. Application of low-dose IL-2 expands Tregs but also activates NK and CD8+ T cells. It was recently shown that graft-specific Tregs recognizing mismatched MHC I molecules via a chimeric antigen receptor were far more potent than polyclonal Tregs in the regulation of immune responses after solid organ transplantation in a humanized mouse model. Therefore, our aim was to enhance the function and stability of transferred CAR-Tregs via expression of membrane-associated IL-2 (mbIL-2). mbIL-2 promoted higher survival, phenotypic stability, and function among CAR-Tregs than observed in clinical trials. The cells were also more stable under inflammatory conditions. In a preclinical humanized mouse model, we demonstrated that mbIL-2 CAR Tregs survive better in the Treg niche than control CAR Tregs and are even resistant to CNI therapy without affecting other Tregs, thus acting mainly in cis. The functional and phenotypic improvements observed after membrane-attached IL-2 expression in CAR-Tregs will be important step for enhancing CAR-Treg therapies currently being tested in clinical trials for use after kidney and liver transplantation as well as in autoimmune diseases.